Onset of summer monsoon in Bangladesh - MOWLA, K. Q. (MAUSAM, 1978)
The onset of summer monsoon in Bangladesh has been studied by the author in this paper with the help of (i) Rainfall in June 1976 in Bangladesh, (ii) Vertical cross-sections of zonal wind for a number of days of June 1976 along Long. 90oE with particular reference to the influence exerted by the easterly jet stream on the onset of summer monsoon in Bangladesh and (iii) The APT pictures received from NOAA-4 for a number of specific days of June 1976. The author concludes that the onset of summer monsoon in Bangladesh is heralded by a sudden increase of rainfall and that the influence of the easterly jet stream appears to extend downwards upto the ground level, removing the westerly component of wind and establishing a secondary core of the easterly jet above Bangladesh at the time of onset of summer monsoon. The APT picture indicated approach and presence of huge masses of convective clouds over Bangladesh at the time of onset of monsoon and during the lull period of summer monsoon, these convective clouds remained away from Bangladesh. The author believes that many of the secrets of summer monsoon of south Asia may be revealed if further understanding of all aspects of the easterly jet stream is achieved.